"The 'Cats' from Hell": The Long Shadow of Poe's Feline in the Short Fiction of Flannery O'Connor and Stephen King. Issue 1 (2nd February 2022) - Correoso-Rodenas, José Manuel
In one of his most famous stories ever written, "The Black Cat" (1843), Edgar Allan Poe chose an animal as a protagonist. However, this pet was going to have an afterlife as one of the most devilish creatures created by the pen of the Bostonian. More than a century later, Flannery O'Connor included a story in her MFA Thesis entitled "Wildcat." Years later, in 1955, her most recognized story, "A Good Man Is Hard to Find, " was published. Both narratives include a cat, in this case not as a main "character, " but as the element that triggers the subsequent tragedy. In 1977, the magazine Cavalier published a short story byStephen King under the title of "The Cat from Hell." King's cat also drives its owner to physical and mental destruction, as Pluto, the wildcat, and Pitty Sing had done before it. This article is based on how three stories (O'Connor's "Wildcat" –1947– and "A Good Man Is Hard to Find" –1955– and King's "The Cat From Hell" –1977–) recreate the characters of the anonymous cat and of Pluto in their pages Moreover, this article also intends to prove the influence of Poe's "The Black Cat" on authors like Flannery O'Connor and Stephen King.